What are the best quorum rules?: A laboratory investigation - Aguiar-Conraria, Luís; Magalhães, Pedro C.; Vanberg, Christoph (Discussion paper series, 2019)
Many political systems with direct democracy mechanisms have adopted rules preventing decisions from being made by simple majority rule. The device most commonly added to majority rule in national is a quorum requirement. The two most common are the participation and the approval quora. Such rules are a response to three major concerns: the legitimacy of the referendum outcome, its representativeness (the concern with the outcome representing the will of the whole electorate), and protection of minorities regarding issues that should demand a broad consensus. Guided by a pivotal voter model, we conduct a laboratory experiment to investigate the performance of different quora in reaching such goals. We introduce two main innovations in relation to previous work on the topic. First, part of the electorate goes to the polls out of a sense of civic duty. Second, we test the performance of a different quorum, the rejection quorum, recently proposed in the literature. We conclude that, depending on the preferred criterion, either the approval or the rejection quorum is to be preferred.
Keywords: Graue Literatur